COMPUTER AIDED LEARNING - Chawla, Preety (SCHOOL SCIENCE, 2010)
With the advent and rapid expansion in Information and Communication Technology, the access to higher education is being expanded enormously and fundamentally changing the models of education. Today, with the use of technology, education has become more learner centric, individualised, interactive and relevant to learner’s needs, thus making it truly a life long learning. Higher education can no longer be considered as a campus-based education for students. The arrival of computer and later internet has opened a much wider horizon for education. Computers have taken over every conceivable field of operation today.